Lack of awareness of pedagogical and Linguistics Certifications that FLD Senior Students might take to be allowed to teach at national and international institutions - Arévalo Idalgo, Dulce Emperatriz Azucena
Getting graduated is one of the main goals for all the students who are already on track with their university studies, and validate all the new knowledge seems to be the key to success. But after reaching the graduating ceremony, is there any other process to follow in order to get a job related with the major already completed? Are students, from the University of El Salvador particularly from the Foreign Language Department, from the English teaching option major, aware of such processes? Certifications are an important part, not only for their professional development, but also they open opportunities to get better job positions, teaching abroad and why not continuing to study in the country or with a scholarship overseas. These are only some of the benefits that can be reached with an English certification. The starting point of this research will provide solid evidence how important the English Language is around the world, and its influence with the aims to validate nonnative English Speakers, with the standards of global English. There are different types of English certifications in the field of education. However, the group will focus on two main types: pedagogical and linguistics; they will be divided depending on the different institutions that hold and administer them; a description of each certification will be included providing the purpose of them and what they evaluate.